Evaluating the efficiency of phiC31 integrase‐mediated monoclonal antibody expression in CHO cells. (30th September 2016) - Ahmadi, Maryam; Mahboudi, Fereidoun; Akbari Eidgahi, Mohammad Reza; Nasr, Reza; Nematpour, Fatemeh; Ahmadi, Samira; Ebadat, Saeedeh; Aghaeepoor, Mojtaba; Davami, Fatemeh
Abstract : Traditional methods to generate CHO cell lines rely on random integration(s) of the gene of interest and result in unpredictable and unstable protein expression. In comparison, site‐specific recombination methods increase the recombinant protein expression by inserting transgene at a locus with specific expression features. PhiC31 serine integrase, catalyze unidirectional integration that occurs at higher frequency in comparison with the reversible integration carried out by recombinases such as Cre. In this study, using different ratios of phiC31 serine integrase, we evaluated the phiC31 mediated gene integration for expression of a humanized IgG1 antibody (mAb0014) in CHO‐S cells. Light chain (LC) and heavy chain (HC) genes were expressed in one operon under EF1α promoter and linked by internal ribosome entry site (IRES) element. The clonal selection was carried out by limiting dilution. Targeted integration approach increased recombinant protein yield and stability in cell pools. The productivity of targeted cell pools was about 4 mg/L and about 40 µg/L in the control cell pool. The number of integrated transgenes was about 19 fold higher than the control cells pools. Our results confirmed that the phiC31 integrase leads to mAb expression in more than 90% of colonies. The productivity of the PhiC31 integrated cell pools was stable for three months in the absence of selection as compared with conventional transfection methods. Hence, utilizing PhiC31 integrase can increase protein titer and decrease the required time for protein expression. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1570–1576, 2016